Pengaruh Kompetensi Sumber Daya Manusia, Pendidikan Dan Pelatihan Serta Peran Pendamping Desa Terhadap Efektivitas Penggunaan Sistem Keuangan Desa Di Kecamatan Galela Barat: The Influence of Human Resource Competence, Education and Training, and the Role of Village Facilitators on the Effectiveness of the Village Financial System in West Galela District - Sahrul Hi. Posi; Delsintia Bitoko; Suharli Manoma (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2026)
This study aims to examine the influence of human resource competency, education and training, and the role of village facilitators, both partially and simultaneously, on the effectiveness of the Village Financial System (Siskeudes) in West Galela District. Using a quantitative approach, this study collected primary data from 35 respondents through saturated sampling techniques and analyzed using multiple linear regression methods. The results of the hypothesis testing indicate that partially, education and training and the role of village facilitators have a positive and significant effect on the effectiveness of Siskeudes use. Conversely, HR competency does not have a significant effect on the effectiveness of the system. However, simultaneously, the three independent variables are proven to have a significant effect on the effectiveness of Siskeudes use. The coefficient of determination (R2) analysis shows a value of 0.568, which means that 56.8% of the variation in the effectiveness of Siskeudes use can be explained by HR competency, education and training, and the role of village facilitators. The remaining 43.2% is influenced by other factors not discussed in this study.